The Baltic states join the Eurozone - Eugenia Martinaityte (Journal of Contemporary Economic and Business Issues, 2016)
The new ongoing world economy processes and political events have affected the Baltic countries. All these countries faced in a short time the complex of environmental conditions as the pressure of EU debt crisis, weak euro against the dollar, the Russian-Ukraine conflict, sanctions against Russia, prices of oil and gas. However, all Baltic countries have had quick recoveries from the recent recession, while their economies had different shape before the crisis. The object of this research is the short time effects on Baltics 'by joining the single currency system. The method used for investigation - comparative statistical analysis using the Eurostat database and national statistics. The study is directed at investigating the impact of changeovers of the national currency to the euro on macro trends and consumer and business expectations. For this purpose, the changes in macroeconomic indicators during the time before and in the aftermath in each country are presented in the context of integration. The result of this study suggests that statistically significant positive effect on macroeconomic and expectation indicators show the importance of joining the single currency system.
Keywords: E3; E5; F4; E58; 330; Baltic States; currency regime; Eurozone; indicators